2021
DOI: 10.1007/s12149-021-01675-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal metabolic response to mRNA COVID-19 vaccinations in oncology patients

Abstract: Background mRNA COVID-19 vaccines are known to provide an immune response seen on FDG PET studies. However, the time course of this metabolic response is unknown. We here present a temporal metabolic response to mRNA COVID-19 vaccination in oncology patients undergoing standard of care FDG PET. Methods 262 oncology patients undergoing standard of care FDG PET were included in the analysis. 231 patients had at least one dose of mRNA COVID-19 vaccine while 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Eight weeks following the vaccination, axillary lymph node uptake was no longer significantly different from unvaccinated patients. The frequency of positive axillary lymph nodes on PSMA-ligand PET/CT examinations in our series is comparable to recently published data for 18 F-FDG PET/CT examinations following COVID-19 vaccinations (1)(2)(3)(4)(5)13,17). It is well established that activated lymphatic cells show increased metabolic activity and consequently accumulate more 18 F-FDG.…”
Section: Discussionsupporting
confidence: 89%
“…Eight weeks following the vaccination, axillary lymph node uptake was no longer significantly different from unvaccinated patients. The frequency of positive axillary lymph nodes on PSMA-ligand PET/CT examinations in our series is comparable to recently published data for 18 F-FDG PET/CT examinations following COVID-19 vaccinations (1)(2)(3)(4)(5)13,17). It is well established that activated lymphatic cells show increased metabolic activity and consequently accumulate more 18 F-FDG.…”
Section: Discussionsupporting
confidence: 89%
“…However, the maximal standardized uptake value (SUVmax) should not be solely used to differentiate between benign and malignant lymph nodes ( 14 ). There were attempts to improve the diagnostic rate by comparing the SUVmax of the ipsilateral lymph nodes to the contralateral lymph nodes ( 27 ) as well as the increased uptake in the deltoid muscle ( 28 , 29 ) or using different tracers ( 30 ). PET is the most sensitive imaging modality for differentiating lymphadenopathy, whereas the radioactive nature and high cost are limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of PET study in oncologic patients might be impacted especially in head and neck cancer, breast cancer or lymphoma in which supraclavicular and axillary lymph node metastases are suspected. Hence, Advani et al [ 1 ] suggest that FDG PET study should be performed at least 2 weeks after vaccination to reduce the interference of lymphadenopathy causing by vaccination in PET interpretation.…”
mentioning
confidence: 99%
“…For patients receiving the third booster dose of mRNA vaccine, the incidence of VAHL at the axillary and supraclavicular regions during 11–15 days and at least 16 days from the booster dose were 17.7% and 2.8%, respectively [ 4 ]. Thus, performing an FDG PET study more than 2 weeks after vaccine administration as suggested by Advani et al [ 1 ] might be applicable to oncologic patients who receive the third booster shot since the incidence of VAHL was low during the recommended period.…”
mentioning
confidence: 99%